Conversations about Aboriginal Work Experiences: Reflections for Community Members, Organizations, and the Academy - Adair, Wendi L.; Kwantes, Catherine T.; Stonefish, Twiladawn; Badea, Ruxandra; Weir, Warren (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2017)
The authors relate how they reflected upon, understood, and shared conversations about Aboriginal experiences at work across time and with different audiences. They found nuances in their understanding and interpretation as their audience changed from sharing circle members, to Cando conference attendees, and finally the Academy. Whereas initial impressions highlighted concepts of strength and resilience, which the authors translated into practical recommendations for mentorship and cultural safety, the results from an academic analysis highlighted how conversational focus changed when participants discussed work experiences in the past (systemic barriers emphasized), present (Indigenous worldviews emphasized), and future (all concepts discussed equally). The authors offer suggestions for continuing the conversation and new ways of understanding Indigenous employees' experiences at work.